THE STRUCTURE OF THE TRAINING PROCESS IN INDIVIDUAL SPORTS CLASSES (Conferencea, 2023)
As a rule, the lesson consists of introductory and preparatory, main and final parts, which is due to the natural changes in the functional state of the athlete's body during work. In this article highlights of the structure of the training process in individual sports classes.